The Use of A Static Mixer for The Coagulation Unit in The Duren Seribu II Water Treatment Plant - Sheryline Putri Chandra Sari; Riana Ayu Kusumadewi; Winarni Winarni (Department of Environmental Engineering - Universitas Pasundan - Indonesia, 2023)
In the drinking water treatment plant involves a significant component i.e., coagulation, which distributed coagulants vastly and equally through rapid stirring for destabilizing colloids and suspended particles in the raw water. In water treatment plants, coagulation units are often classified into mechanical and hydraulic coagulation. This study aimed to discover the use of and in-line static mixers as coagulation in designing the Duren Seribu II Drinking Water Treatment Plant (WTP). The design criteria for coagulation unit in Duren Seribu II WTP was determined by comparing several data obtained from literature studies and evaluation of the existing conditions of Duren Seribu I WTP. Duren Seribu I WTP was evaluated by direct measurement in the field. From the results of data analysis, the design criteria appropriate for Duren Seribu II WTP, the G value is 2078.07 sec-1, the detention time (td) is 4 sec, and the G.td value is 8352.19.